The mth term of a H.P. is n snd th nth term is m.Prove that pth term is mn/p?

Asked by  | 6th Jul, 2008, 11:05: PM

Expert Answer:

let H.P. be 1/a , 1/(a+d) , 1/(a+2d),....

then given a+(m-1)d = 1/n

and a+(n-1)d = 1/m

solving for a and d we get a = 1/mn  and d = -1/mn

then a+(p-1)d= 1/mn + (p-1)(-1/mn) = p/mn

so pth term of H.P. will be 1/(a+(p-1)d) = mn/p

Answered by  | 12th Sep, 2008, 12:21: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.